2021
DOI: 10.3390/antiox10091430
|View full text |Cite
|
Sign up to set email alerts
|

Ergosta-7,9(11),22-trien-3β-ol Attenuates Inflammatory Responses via Inhibiting MAPK/AP-1 Induced IL-6/JAK/STAT Pathways and Activating Nrf2/HO-1 Signaling in LPS-Stimulated Macrophage-like Cells

Abstract: Chronic inflammation induces autoimmune disorders and chronic diseases. Several natural products activate nuclear factor erythroid 2-related factor 2 (Nrf2) signaling, attenuating inflammatory responses. Ergosta-7,9(11),22-trien-3β-ol (EK100) isolated from Cordyceps militaris showed anti-inflammatory and antioxidative activity, but those mechanisms are still unclear. This study is the first to investigate EK100 on antioxidant Nrf2 relative genes expression in LPS-stimulated macrophage-like cell lines. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In this study, the functional enrichment of the collection of Co-genes and the Top 11 Hub Genes included the regulation of IL-6 production, and the Upstream Pathway of the key gene (CASP1) was closely related to the JAK-STAT signaling pathway. The JAK/STAT pathway, also called the IL-6 signaling pathway, can be activated by IL-6 ( 198 , 199 ), which is also a significant indication of COVID-19 severity ( 1 , 200 ). Activation of the JAK/STAT pathway, which produces pro-inflammatory cytokines, also a significant role in the development of rheumatoid arthritis (RA) ( 201 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the functional enrichment of the collection of Co-genes and the Top 11 Hub Genes included the regulation of IL-6 production, and the Upstream Pathway of the key gene (CASP1) was closely related to the JAK-STAT signaling pathway. The JAK/STAT pathway, also called the IL-6 signaling pathway, can be activated by IL-6 ( 198 , 199 ), which is also a significant indication of COVID-19 severity ( 1 , 200 ). Activation of the JAK/STAT pathway, which produces pro-inflammatory cytokines, also a significant role in the development of rheumatoid arthritis (RA) ( 201 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atomic force microscopy assay (AFM) can precisely measure the appearance of cells down to the nanometer scale, which can be used to explore the precise and subtle three‐dimensional morphology information of cells 23 . Cultured cells at the number of 5 × 10 4 cells in the well were attached to round glass coverslips in 6‐well plates and treated with PW06 0.2 μM for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…demonstrated that LPS could also induce the production of IL-6, TNF-α, and phosphorylated janus kinase (JAK). This increasing pro-inflammatory mediator expression is associated with the phosphorylation of MAPKs within 15–30 min after LPS stimulation ( 46 48 ). MAPK signaling pathway leads to the release of TNF-α and IL-6.…”
Section: Pathogenic Mechanism Of Periodontitismentioning
confidence: 99%
“…The latter could bind to the transmembrane IL-6 receptor and subsequently activate JAK, followed by the phosphorylation of the signal transducer and activator of transcription (STAT) 1/3. STAT1/3 could bind to the specific target DNA and trigger the inflammatory cytokines of TNF-α, IL-2, and IL-6 eventually ( 46 ). Besides, in the NF-κB signaling pathway, the phosphorylation of MAPK could lead AP-1 together with JNK and p38 to translocate into the nucleus and result in the upregulation of the proinflammatory cytokines ( 29 , 30 ).…”
Section: Pathogenic Mechanism Of Periodontitismentioning
confidence: 99%